Acute haemorrhagic pericarditis: an unusual presentation of Chlamydophila pneumoniae pneumonia infection. (2nd July 2020) - Oztek Celebi, Fatma Zehra; Fettah, Ali; Yesil, Sule; Yoldas, Tamer; Tanir, Gonul; Akcaboy, Meltem; Senel, Saliha
ABSTRACT: Chlamydophila pneumoniae:, a common cause of respiratory tract infections, rarely leads to serious conditions. A 13-year-old boy with serologically confirmed C. pneumoniae infection presented with pneumonia complicated by pericardial and bilateral pleural effusions. He had a large haemorrhagic pericardial effusion from which 1000 ml of fluid was aspirated over 10 days and a right haemorrhagic pleural effusion which required a chest drain and the removal of 700 ml over 5 days. The addition of clarithromycin to ceftriaxone appeared to enhance recovery. As far as we are aware, this is the first report in the English literature of massive haemorrhagic pericardial and pleural effusions in children owing to C. pneumoniae infection.